PETROGRAPHY OF GABRO-DOLERITES OF ZVIZDAL-ZALESYE DYKE - MYTROKHYN, O.; OMELCHENKO, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New data about the composition and texture features of Zvizdal-Zalesye dyke rocks have been received on the base of revision studies of drill-core samples. Conclusions about the inner structure, the genesis and the belonging to some magmatic formation of region have been done. It is supposed that subalkaline olivine leucodolerites of Zvizdal-Zalesye dyke were the final episode of subalkaline high-aluminous basalts intruded from Korosten Pluton deep magma chamber.